EFFECT OF SUBMUCOSAL AND INTRAMUSCULAR DEXAMETHASONE ON POSTOPERATIVE SEQUELAE AFTER MANDIBULAR THIRD MOLAR SURGERY: A COMPARATIVE STUDY - Dr. Ajay Kumar Kushwaha; Dr. Gaurav Singh; Dr. Ashok Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Surgical extraction of impacted mandibular third molars is commonly associated with postoperative pain, swelling, and trismus. Dexamethasone, a corticosteroid, is often used to reduce these sequelae, but the comparative efficacy of different administration routes remains underexplored. Objective: To compare the effectiveness of intramuscular and submucosal dexamethasone with a control group in managing postoperative complications following mandibular third molar surgery. Materials and Methods: A prospective, randomized clinical study was conducted at Sardar Patel Post Graduate Institute of Dental and Medical Sciences, Lucknow. 90 patients with mesioangular Class II Position B mandibular third molar impactions were randomly divided into three groups: Group A received 8 mg dexamethasone intramuscularly (deltoid), Group B received 8 mg submucosally at the surgical site, Group C received no dexamethasone (control). Postoperative parameters including pain (Visual Analog Scale), swelling (facial measurements), and trismus (interincisal distance) were evaluated on postoperative days 1, 3, and 7. Data were analyzed using ANOVA and post-hoc Tukey test, with p < 0.05 considered statistically significant. Results: On day 1, mean pain scores were lowest in Group B (3.0 ± 1.1), followed by Group A (3.9 ± 1.2), and highest in Group C (5.2 ± 1.0), (p = 0.001). Maximum swelling on day 3 was observed in Group C (6.7 ± 1.3 mm) versus Group A (5.1 ± 1.0 mm) and Group B (4.3 ± 0.8 mm), (p = 0.002). Trismus reduction was significantly better in Group B by day 7 (interincisal opening: 40.1 ± 2.5 mm) compared to Group A (37.8 ± 2.9 mm) and Group C (35.4 ± 3.1 mm), (p = 0.003). Conclusion: Submucosal dexamethasone was more effective than intramuscular injection and no steroid treatment in reducing postoperative complications after mandibular third molar surgery, making it a preferable route for clinical practice.